1971
DOI: 10.1159/000208563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experiences with Cytotoxic Immunosuppressive Treatment of Idiopathic Thrombocytopenic Purpura

Abstract: After a review of the literature, a series of 21 patients with ITP treated with non-steroidal immunodepressive agents is presented. The agents were azathioprine (AZP), methotrexate (MTX), cyclophosphamide (CPH), vinblastine (VLB) and L-asparaginase (L-ase). No permanent, unmaintained remission in chronic, self-perpetuating cases of ITP could be obtained, even after splenectomy. However, AZP was useful in the treatment of chronic cases, either alone or in combination with steroids, where it displayed a useful s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Immunosuppressive therapy has been administered to small uncontrolled groups of children with dubious results (8,9). In our study, only 2 patients received immunosuppressive therapy; 1 of the 2, who demonstrated bleeding tendency after splenectomy, responded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppressive therapy has been administered to small uncontrolled groups of children with dubious results (8,9). In our study, only 2 patients received immunosuppressive therapy; 1 of the 2, who demonstrated bleeding tendency after splenectomy, responded.…”
Section: Discussionmentioning
confidence: 99%
“…Several therapeutic options are available for children with chronic ITP, including high-dose iv gamma globulin (IV IG) (2), anti-D (3), high-dose steroids (3,4), splenectomy (5-7) and immunosuppressive therapy (5,8,9). The specific indications for each therapeutic regimen and for the "wait and see" policy are not clear (10,11).…”
mentioning
confidence: 99%
“…Vincristine and vinblastine have been found to raise the peripheral platelet couint in a wide variety of clinical thrombocytopenic puirpturas. Some investigators have suiggested that stuppression of the immtune response is the mechanism uinderlying the thrombocytosis (17). This however, cannot explain the thrombocytosis indtuced in secondary thrombocytopenias or in patients with initially normal platelet counts.…”
Section: Resultsmentioning
confidence: 99%
“…Vincristine and vinblastine have since been shown to have a therapeutic effect in thrombocytopenias of varying etiologies (13)(14)(15)(16). Although immunosuppression (14,17) and alterations in platelet release (18) have been suggested as possible underlying mechanisms, laboratory investigations have suggested that the thrombocytosis was secondary to an increase in marrow production, resulting from an increase in number, size, and ploidy of megakaryocytes (19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Many therapeutic approaches have been sug gested [1,2,3,17,19], but they are neither harmless, nor do they bring true advantages [ 15], It is widely accepted that a majority of patients the pathogenesis of ITP involves immune-mediated pro cesses, and almost all therapeutic protocols are based on the attempt to interfere with the immunologic mechanisms [19], Recently, several studies have de monstrated that pulse methylprednisolone (MP) ther apy is effective in controlling immunological diseases [6,7,21,23]. The successful use of intravenous pulses of MP has been reported in a woman with ITP [24], We reported an improvement of the disease in 2 chil dren affected with chronic ITP [20].…”
Section: Introductionmentioning
confidence: 99%